ANALISIS FAKTOR-FAKTOR PENYEBAB KEENGGANAN MASYARAKAT MEMBAYAR ZAKAT MELALUI INSTANSI BAZIS/LAZ DI KOTA MEDAN ( Studi Kasus : Masyarakat Kecamatan Medan Tembung ) - Abdul Hafiz Daulay; Iryad Lubis (Departemen Ekonomi Pembangunan USU, 2015)
The objective of the research was to find out some factors which caused people to be reluctant to pay/extend their zakat (obligation to contribute to the poor or to religious activities) through BAZIS/LAZ institution, Medan Tembung Subdistrict, Medan, and to analyze some measures and policy which will be taken by BAZIS/LAZ.. The samples were 100 respondents in Medan Tembung Subdistrict, taken by using simple random sampling technique. The data were gathered by distributing questionnaires and analyzed by using descriptive analysis with an SPSS (Statistic Product and Service Solution) version 16 software program.The result of the research showed that the most dominant factor which caused people to be reluctant to pay/extend their zakat through BAZAS/LAZ was religious factor (they felt it was better to donate zakat directly to mustahiqs (the poor and needy) who were still their relatives (33%), followed by location (the location of BAZIS/LAZ was far from their residence) (24%), service (the service provided by BAZIS/LAZ was not satisfactory) (21%), credibility (people did not trust BAZIS/LAZ in distributing zakat to the needy since the management of extending zakat was not transparent) (12%), and income (high income people would rather extend their zakat through organized BAZIS/LAZ) (10%). 88% of the people in Medan Tembung Subdistrict were reluctant to pay/extend their zakat through BAZIS/LAZ, and only 12% of them who paid/extended their zakat through BAZIS/LAZ. They wanted BAZIS/LAZ institution to be professional, managerial, and transparent and to improve its service.Keywords: Reluctance, Zakat, Policy